Ukranian-Russian Conflict and Its Influence on The Political Speeches: A Discourse Analysis Study 0f The Use of Interpersonal Elements - Arsiyana, Marliza (Universitas Negeri Semarang, 2025)
On the 24th February 2022, President Vladimir Putin ordered Russian troops to conduct